Pengembangan Sistem Kontrol Navigasi Kursi Roda Cerdas Menggunakan Arsitektur Subsumption Studi Kasus Door Passing Dan Corridor Following - Setiawan, Iwan; Darjat, Darjat; Gusman Namara, Rano (Transmisi, 2008)
Several research have shown that both children and adults benefit substantially from access to a means of independent mobility. While the needs of many individuals with disabilities can be satisfied with traditional manual wheelchairs, a segment of the disabled community finds it difficult or impossible to use wheelchairs independently. To accommodate this population, researchers have used technologies originally developed for mobile robots to create "smart wheelchairs." Smart wheelchairs have been the subject of research since the early 1980s. Our goal in this project is to develop a smart wheelchair with a human friendly interface for high-level controlThere are two main capability that we embedded in this wheelchairs (1) Obstacle avoidance and (2) Door passing. From the experiment result,those capability seems to be work, but there must be enchanment due to  wheelchairs comportability.Keywords  : Kursi Roda Cerdas, Arsitektur Subsumption, Joystick, Sensor UltrasonikPermalink: http://ejournal.undip.ac.id/index.php/transmisi/article/view/1603